Bacillus coagulans and Clostridium butyricum synergistically alleviate depression in a chronic unpredictable mild stress mouse model through altering gut microbiota and prefrontal cortex gene expression - Xu, Jingyi; Zhou, Lei; Chen, Zhaowei; Wang, Yuezhu; Xu, Fang; Kuang, Qun; Zhang, Yixuan; Zheng, Huajun (Frontiers in Pharmacology, 2024)
The prevalence of major depressive disorder (MDD) has gradually increased and has attracted widespread attention. The aim of this study was to investigate the effect of a probiotic compound consisting of Bacillus coagulans and Clostridium butyricum, on a mouse depression model. Mice were subjected to chronic unpredictable mild stress (CUMS) and then treated with the probiotics at different concentrations. The probiotics improved depressive-like behavior in CUMS mice, as indicated by decreased immobility time (p < 0.05) in the forced swimming test and tail suspension test.Probiotics intervention also increased the level of 5-hydroxytryptamine (5-HT) in the prefrontal cortex (PFC) and decreased the adrenocorticotropic hormone (ACTH) level in serum. In addition, by comparing the PFC gene expression among different groups, we found that downregulated genes in CUMS group such as Sfrp5and Angpt2, which were correlated with depression, were reversed by the probiotics. Moreover, we found that the genes upregulated by probiotics were enriched in the PI3K-Akt signaling pathway. Furthermore, the probiotics altered the structure of the gut microbiota, and reversed the reduction of cob(II)yrinate a,c-diamide biosynthesis I pathway in CUMS group. Several species like Bacteroides caecimuris and Parabacteroides distasoni, whose abundance was significantly decreased in the CUMS group but reversed after the probiotics intervention, showed significantly positive correlation with depression associated genes such as Tbxas1 and Cldn2. These findings suggested that CUMSinduced depression-like behavior can be alleviated by the probiotics, possibly through alterations in the PFC gene expression and gut microbiota.